Was pharmacy their preferred choice? Assessing pharmacy students’ motivation to study pharmacy, attitudes and future career intentions in Sierra Leone - James, Peter Bai; Batema, Moses Nathanael Pessima; Bah, Abdulai Jawo; Brewah, Tima Sannah; Kella, Alphan Tejan; Lahai, Michael; Jamshed, Shazia Qasim (Elsevier B.V., 2018)
Background There is a dearth of skilled pharmaceutical workforce in the African region, and this is partly due to a limited number of prospective students entering the profession. An understanding of the factors that influence the choice of pharmacy as a career is needed to attract highly motivated and skilled individuals into the profession. Therefore, the objective of this study was to assess pharmacy students’ motivation to study pharmacy, their attitude and future career intentions in Sierra Leone.